Enterprise data governance : reference & master data management, semantic modeling - Bonnet, Pierre, active 1585-1600 (London : ISTE, 2010)
In an increasingly digital economy, mastering the quality of data is an increasingly vital yet still, in most organizations, a considerable task. The necessity of better governance and reinforcement of international rules and regulatory or oversight structures (Sarbanes Oxley, Basel II, Solvency II, IAS-IFRS, et cetera.
A company and its data -- Strategic aspects -- Taking into account business software -- Return on investment -- MDM maturity levels and the model-driven MDM -- Data governance functions -- Organizational aspects -- The semantic modelling framework -- Semantic modeling procedures -- Logical data modeling -- Organization modeling -- Technical integration of the MDM.
Includes bibliographical references and index.
Keywords: Data protection